1994
DOI: 10.1007/bf00714575
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular calcium in pregnancy-induced attenuation of phenylephrine contraction in rat aorta with functional endothelium

Abstract: The effect of pregnancy on the supply of calcium ions for the contractile responses of rat aortic rings to phenylephrine was investigated. The contractility of intact aortic rings from pregnant rats, compared with that of similar rings from non-pregnant rats, to phenylephrine and potassium chloride was significantly decreased. Contractions of rings from non-pregnant rats, pretreated with phenylephrine or potassium chloride, in response to calcium chloride were greater than those of similarly treated rings from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
3
9
1
Order By: Relevance
“…The mechanisms involved are similar in some respects to those described for tissues from normal pregnancy in that they are endothelium-dependent, involve enhanced relaxation to acetylcholine and increased activity of the Na + -K + ATPase, are not affected by treatment with indomethacin and do not involve changes in intracellular release of calcium. However, unlike the observations previously reported for normal pregnancy [17,19], the contractile responses to KCl were not significantly diminished, and the responses to CaCl 2 were unaltered. The nonpregnant source of the tissue may explain the differences.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The mechanisms involved are similar in some respects to those described for tissues from normal pregnancy in that they are endothelium-dependent, involve enhanced relaxation to acetylcholine and increased activity of the Na + -K + ATPase, are not affected by treatment with indomethacin and do not involve changes in intracellular release of calcium. However, unlike the observations previously reported for normal pregnancy [17,19], the contractile responses to KCl were not significantly diminished, and the responses to CaCl 2 were unaltered. The nonpregnant source of the tissue may explain the differences.…”
Section: Discussioncontrasting
confidence: 82%
“…We have previously reported that, in vitro, the mechanisms of attenuated vascular response in pregnancy involve the vascular endothelium [15] and include enhanced acetylcholine-induced relaxation [16], increased functional activity of the Na + /K + ATPase [5], reduced extracellular influx of calcium reduced with no change in intracellular release of calcium [17], and insensitivity to indomethacin [15,16]. This study investigated the possibility that these changes could be duplicated in aortic rings from nonpregnant rats, exposed to mild hypo-osmolarity achieved by manipulation of [Na + ] e , and therefore provide an explanation for the attenuated vascular reactivity in normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…*** P < 0.0001, ** P < 0.01 Vascular reactivity is modulated by the endothelium through the production of vasodilators, such as nitric oxide, prostacyclin, endothelium-derived hyperpolarising factor and vasoconstrictors, such as endothelium-derived constricting factor, endothelin and thromboxane [8]. In normal pregnancy, there is endothelium-dependent attenuation of vascular reactivity, which involves enhanced production of vasodilators [1,2,7,21]. However, the contractionattenuating effect of hCG is unlikely to be the result of increased production of nitric oxide, since the application of L-NMMA in this study (to block nitric oxide synthase) did not normalise the contractile responses to phenylephrine.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism of the pregnancy-induced decrease of vascular pressor responsiveness to these hormones has not yet been clarified. Downregulation of specific receptors (2,13,18), enhanced secretion of vasodilatory substances (9), and alterations of receptor-response coupling (uncoupling) (8,11,28,29,34) have been considered as mediators of decreased vasopressor response to these hormones.…”
mentioning
confidence: 99%
“…A gestational alteration of the vascular L-VDCC has already been suggested. For example, activation of the channel as induced by depolarization or Bay K 8644 (BAY), a specific L-VDCC agonist (31), was observed to be a less potent signal for vascular constriction in aortic rings and mesenteric arteries of pregnant than nonpregnant rats (11,28,29,34). In addition, chronic estrogen administration was noted to decrease the number of L-VDCC (26).…”
mentioning
confidence: 99%